Kajian Tingkat Kenyamanan Berdasarkan Termal Humidity Index (THI) Lanskap Jalan Soekarno Hatta Kota Malang - Rizki Alfian; Nuraini Nuraini (Universitas Tribhuwana Tunggadewi, 2019)
Streets as part of the city's landscape that support the function and activities of the city. Each street in the city area has a streetscape which aims to support the users activities. Soekarno Hatta street is one of the protocol street in Malang city with the track area which is quite famous and one of the loud route in Malang City. This research aims to: 1) identify vegetation on the streetscape on Soekarno Hatta street; 2) analyze thermal comfort on the Soekarno-Hatta streetscape. Based on the observation, it is known that the trembesi population dominates at the Soekarno Hatta streetscape. Soekarno Hatta street has an average temperature of 31.1 ° C and an average humidity of 57%. Soekarno Hatta street has THI value of 28.43 whereas THI value which is categorized as comfortable is between 21 - 27. Based on the physical observation on Soekarno Hatta streetscape needs to be done vegetation arrangement because the vegetation in Soekarno Hatta Street has a high density of trees that will interfere with canopy growth when reaching the maximum size. Selection of appropriate shade vegetation and regular maintenance is expected to improve the comfort level in each way. In addition to vegetation, the physical condition of the pedestrian on Soekarno Hatta Road also needs a redesign to support the comfort of pedestrians.